2015
DOI: 10.1111/birt.12152
|View full text |Cite
|
Sign up to set email alerts
|

Previous Breastfeeding Experience and Duration of Any and Exclusive Breastfeeding among Multiparous Mothers

Abstract: Multiparous women with no previous breastfeeding experience and those with a short duration of previous breastfeeding should be provided with greater support to promote a longer duration of breastfeeding. Multiparous women with a longer duration of breastfeeding should be strongly encouraged to meet or exceed this duration with their current infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
1
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 33 publications
(55 reference statements)
9
57
1
14
Order By: Relevance
“…Findings of other studies also emphasized that social supports regarding working conditions (such as delivery leave for parents and flexible working hours) increasing the breastfeeding rate. [2829]…”
Section: Discussionmentioning
confidence: 99%
“…Findings of other studies also emphasized that social supports regarding working conditions (such as delivery leave for parents and flexible working hours) increasing the breastfeeding rate. [2829]…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of breast-feeding have been found in Europe and Australia, compared with the USA and Canada (8) , which encourages us to consider the importance of social/political contexts in shaping features of the home, work and community environments that may support breast-feeding. This includes not returning to employment early (10,14) , parental leave policies and flexible working conditions (12) ; as well as social support, positive cultural norms surrounding breast-feeding and the Rural 1·19 0·99, 1·43 1·14 0·95, 1·37 0·97 0·80, 1·18 0·93 0·77, 1·14 0·77 0·57, 1·06 0·72 0·53, 1·00 Remote 0·93 0·74, 1·18 0·88 0·69, 1·12 0·99 0·79, 1·26 0·94 0·74, 1·20 0·93 0·65, 1·33 0·88 0·61, 0·88, 1·26 1·02 0·85, 1·23 1·16 0·96, 1·40 1·13 0·94, 1·36 1·36 1·01, 1·82 1·33 0·99, 1·79 Always difficult 1·16 0·91, 1·48 1·13 0·88, 1·45 1·14 0·88, 1·48 1·11 0·85, 1·44 1·34 0·91, 1·99 1·31 0·88, 1·95 SEIFA ed/occ quintile 0·92 0·87, 0·98 0·95 0·89, 1·01 0·95 0·89, 1·01 0·97 0·91, 1·03 1·05 0·95, 1·16 1·09 0·98, 1·21 OR1, minimally adjusted for baseline age and birth year of the index child; OR2, minimally adjusted + parent's education; SEIFA, Socio-Economic Indexes for Areas (education and occupation); Ref., reference category. Significant results are indicated in bold font.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal attributes positively associated with breastfeeding initiation and duration include: higher maternal age (6,(8)(9)(10)(11) ; higher maternal education (6,(8)(9)(10)(11)(12)(13) , although not in all studies (10) ; higher family income (8) ; being married (9,11) , although not in all studies (10) ; living with a partner (13) ; history of prior breast-feeding (13)(14)(15) ; and having a healthy pre-pregnancy BMI (16)(17)(18) . Higher parity has also been positively associated with breast-feeding initiation (11) and more frequently with breast-feeding duration (10,19,20) ; while difficulties with infant feeding in the first month postpartum are negatively associated with breast-feeding duration (10) .…”
mentioning
confidence: 99%
“…This lack of a protective association among multiparous mothers is not surprising in Iran and other Middle‐Eastern countries; where breastfeeding initiation is near universal, the majority of children are breastfed well into their first year of life (Abuidhail, ; Al‐Kohji, Said, & Selim, ; Musaiger & Abdulkhalek, ; Olang et al, ) and breastfeeding duration has been reported to be positively associated with multiparty (Al‐Hreashy et al, ; Al‐Sahab et al, ; Batal, Boulghourjian, Abdallah, & Afifi, ; Dashti, Scott, Edwards, & Al‐Sughayer, ). However, this finding is not necessarily generalisable to other countries with lower breastfeeding initiation rates, shorter breastfeeding duration rates, and/or where multiparity has not been found to be associated with breastfeeding outcomes (Bai, Fong, & Tarrant, ; Donnan et al, ; Lok, Bai, & Tarrant, ; Pang et al, ).…”
Section: Discussionmentioning
confidence: 80%
“…Step 6 Step 7 Step 8 Step 9 has not been found to be associated with breastfeeding outcomes (Bai, Fong, & Tarrant, 2015;Donnan et al, 2013;Lok, Bai, & Tarrant, 2015;Pang et al, 2016). Step 5.…”
Section: Characteristicmentioning
confidence: 99%